Environmental policy as a factor of China's food security - Sushchenko Maxim (E3S Web of Conferences)
Public policy tools help to effectively implement the goals of the national development of the People’s Republic of China. The article examines the main directions and mechanisms of environmental policy of modern China as factors of ensuring food security of society. The problems of conservation, environmental protection and food security are closely connected. Agriculture is the only branch of the Chinese economy that is directly related to the country’s natural conditions. Protecting the environment from the adverse effects of anthropogenic factors is the most important condition for achieving China’s strategic goals. The actions of the administrative, economic and regulatory mechanisms of environmental protection of the People’s Republic of China are interrelated and interdependent. The regulatory mechanism includes means of state and party policy of the state of nature. The action of the mechanisms ensures the effective implementation of China’s socio-economic policy in the areas of sustainable environmental management and reduction of environmental pollution.